Costs and Outcomes of Patients Admitted to the Intensive Care Unit With Cancer. (February 2021) - Zheng, Bo; Reardon, Peter M.; Fernando, Shannon M.; Webber, Colleen; Thavorn, Kednapa; Thompson, Laura H.; Tanuseputro, Peter; Munshi, Laveena; Kyeremanteng, Kwadwo
Introduction: Cancer is associated with significant health-care expenditure, but few studies have examined the cost of patients with cancer in the intensive care unit (ICU). We aimed to describe the costs and outcomes of patients admitted to the ICU with cancer. Methods: We conducted a retrospective cohort study of patients admitted between 2011 and 2016 to 2 tertiary-care ICUs. We included patients with a cancer-related most responsible diagnosis using International Classification of Disease, 10th Revision, Canada codes. We compared costs and outcomes of patients having cancer with noncancer controls matched for age, sex, and Elixhauser comorbidity score. We used logistic regression to determine predictors of mortality among patients with cancer. Results: There were 1022 patients with cancer during the study period. Mean age was 63.2 years and 577 (56.5%) were male. Inhospital mortality for all patients with cancer was 24.0%. Total cost per patient was higher for patients with cancer compared to noncancer patients (CAD57 084 vs CAD40 730; P < .001) but there were no differences in the cost per day (CAD2868 vs CAD2887; P = .76) or ICU cost (CAD30 495 vs CAD29 382; P = .42). Among patients with cancer, the cost per day was higher for nonsurvivors (CAD3477 vs CAD2677; P < .001). Liver disease (odds ratio [OR]: 2.96; 95% confidence interval [CI]: 1.22-7.81), mechanical ventilation (OR: 1.73; 95% CI: 1.25-2.39), hematologic malignancy (OR: 3.88; 95% CI: 2.31-6.54), and unknown primary site (OR: 2.13; 95% CI: 1.36-3.35) were independently associated with mortality in patients with cancer. Conclusion: Patients admitted to the ICU with cancer did not differ in cost per day, ICU cost, or mortality compared to matched noncancer controls. Among patients with cancer, nonsurvivors had significantly higher cost per day compared to survivors. Hematologic and unknown primaries, liver disease, and mechanical ventilation were independently associated with mortality in patients with cancer.